A dialogical encounter with teaching practice-based subjects in higher education - Hilde Rustad; Gunn Engelsrud (Journal for Research in Arts and Sports Education, 2022)
The intention of this article is from a phenomenological perspective to “unpack” the role of emotions when teaching practice-based subjects in higher education. When teaching practice-based subjects, educators’ embodied expressions and personal understanding affect both teachers’ and students’ knowledge production. The academic and the political worlds have a vested interest in understanding and improving methods of teaching and learning in higher education, and concepts such as accountability and performativity are used to indicate quality in education, whereas the affective and embodied knowledge tend to be unterminated. In this article, the authors investigate the teacher’s body as a knowledge producing and productive resource in teaching practice-based subjects. Analysis of the dialogue between two teachers shows how expressing the intersubjective and subjective dialogues in- and between them illuminates qualities such as daring to be a bodily perceptive and emotional being, listening within and the experience of teaching and learning simultaneously, trusting bodily sensations, and letting the students be who they are. By applying theoretical concepts to teachers’ descriptions of classroom experiences, this article contributes perspectives and sheds light upon human knowledge in professional relations.